МОРФОДИНАМИКА ЛИНЕЙНЫХ НАСЫПЕЙ В УСЛОВИЯХ СЕВЕРА ЗАПАДНОЙ СИБИРИ - Евдокимов В.И. (My University, 2006)
Author suggests the classification of morphodynamic processes on the linear embankments in the North of West Siberia. It is based on extremely generalized types of ground movements: downward, lateral, complex. The description and examples are given of embankment morphology changes caused by erosion, suffosion, slope processes and coastal dynamics during floods. The classification aims the engineering-geomorphologic purposes and may be used for the maintenance of embankment stability.
Keywords: 551.4.438.5:625.74(571.1)